Control by Ca2+ of mitochondrial structure and function in pancreatic β-cells. (November 2020) - Georgiadou, Eleni; Rutter, Guy A.
Graphical abstract: A reduction in mitochondrial Ca 2+ uptake through altered Mcu expression or impairment of the mitochondrial fusion and fission machinery may be potential pathways towards β-cell failure in type 2 diabetes. Highlights: Mitochondrial Ca 2+ uptake is essential for normal β-cell function and insulin secretion. Changes in mitochondrial ultrastructure are observed in type 2 diabetes and may be driven by altered Ca 2+ homeostasis. mtDNA mutations lead to impaired GSIS and diabetes in rodents and humans. Abstract: Mitochondria play a central role in glucose metabolism and the stimulation of insulin secretion from pancreatic β-cells. In this review, we discuss firstly the regulation and roles of mitochondrial Ca 2+ transport in glucose-regulated insulin secretion, and the molecular machinery involved. Next, we discuss the evidence that mitochondrial dysfunction in β-cells is associated with type 2 diabetes, from a genetic, functional and structural point of view, and then the possibility that these changes may in part be mediated by dysregulation of cytosolic Ca 2+ . Finally, we review the importance of preserved mitochondrial structure and dynamics for mitochondrial gene expression and their possible relevance to the pathogenesis of type 2 diabetes.